Radiographic inspection of porosity in Ti-6Al-4V laser-welded joints - Juliana Maria Costa Nuñez-Pantoja; Jessica Mie Ferreira Koyama Takahashi; Mauro Antônio de Arruda Nóbilo; Rafael Leonardo Xediek Consani; Marcelo Ferraz Mesquita (Sociedade Brasileira de Pesquisa Odontológica, 2011)
Widely used in dentistry, Ti-6Al-4V alloy is difficult to cast and solder, as it frequently exhibits pores inside the structure. This study was conducted to evaluate the effect of joint openings and diameters of laser-welded joints executed in Ti-6Al-4V structures on the presence of pores as checked by radiographic procedures. Sixty dumbbell rods with central diameters of 1.5, 2.0 and 3.5 mm were created from Ti-6Al-4V-wrought bars. Specimens were sectioned and welded using two joint openings (0.0 and 0.6 mm). The combination of variables created six groups (n = 10). Laser welding was executed using 360V/8ms (1.5 and 2.0 mm) and 380V/9ms (3.5 mm), with the focus and frequency set to zero. The joints were finished, polished and submitted to radiographic examination. The radiographs were visually examined for the presence of pores in the joints, qualitatively. The percentage of radiographic presence of pores was calculated without counting pores per joint. Data were analyzed using a chi-square test (α = 0.05). For the 1.5-mm specimens, the incidence of pore presence was significantly higher (p = 0.0001) when using 0.6-mm joint openings (40%) compared to 0.0-mm openings (0%). For the 2.0-mm specimens, there was no significant difference between groups (p = 0.2008). However, for the 3.5-mm specimens, the incidence of pore presence was lower (p = 0.0061) for 0.6-mm openings (50%) compared to 0.0-mm openings (70%). Therefore, laser welding of Ti-6Al-4V structures with thin diameters provides the best condition for the juxtaposition of the parts.